Spent coffee ground as renewable energy source: Evaluation of the drying processes - Tun, Maw Maw; Raclavská, Helena; Juchelková, Dagmar; Růžičková, Jana; Šafář, Michal; Štrbová, Kristína; Gikas, Petros (Journal of environmental management, 2020)
Spent coffee ground (SCG) is an environmental nuisance material, but, if appropriately processed it can be converted into pellets, and thus, used as an energy source. The moisture content of the final product should be below 10%, to ensure safe storage, and elimination of microorganism growth (particularly moulds). The present study aims to identify the optimal drying process for removing moisture from SCG and to investigate changes to the composition of SCG due to drying, at temperatures around 75 °C, so that the dried SCG to qualify as renewable energy source. Three drying processes were employed for SCG drying (with initial moisture content of about 65%): oven drying, solar drying and open air sun drying, while SCG samples were placed in aluminium trays with thicknesses of 1.25, 2.5 and 4 cm. Based on the experimental results for SCG samples with thickness 2.5 cm, the open air sun drying process required 10 h to reach final moisture content of 37%, while solar drying achieved 10% moisture content in 10 h and oven drying achieved 7% moisture content in 6 h. The solar drying process proved as the most advantageous, due to low energy requirements and adequate quality of dried SCG. Also, experiments indicated that SCG storage at "normal room conditions" resulted to equilibrium moisture content in SCG of 8%, regardless of the initial moisture content. Furthermore, instrumental analyses of the SCG, revealed changes to its composition for a number of chemical groups, such as aldehydes, ketones, phytosterols, alkaloids, lactones, alcohols, phenols, pyrans and furans, among others. It was also identified that the SCG colour was affected due to the drying process.
Keywords: teplota; obnovitelná energie; Phenols; Desiccation; Temperature; káva; Coffee; vysoušení; Renewable Energy; fenoly